CHALLENGES IN TRANSLATING CULTURE-SPECIFIC ITEMS: A CASE STUDY OF UZBEK PROVERBS INTO ENGLISH (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This paper investigates the challenges encountered when translating culture-specific items, particularly Uzbek proverbs, into English. It analyzes the linguistic, cultural, and semantic obstacles that arise during translation processes and examines various translation strategies including literal translation, cultural equivalence, and explanatory translation. The research employs a comparative analysis of selected Uzbek proverbs and their English counterparts to identify patterns of cultural divergence and convergence.